Relevance of Presidential Neutrality to achieve of Good governance in Indonesia: A comparative study of Joko Widodo's first and Second Regimes - Nanda Vico Saeful Hakim; Hui Xian Koh (Journal Governance Society, 2024)
The President of the Republic of Indonesia, who has been directly elected in the general election represents a better relationship to the people compared to the previous concept of presidential elections by Consultative Assembly. Indonesian President, who wields significant and central influence, must maintain independence to uphold the integrity and sanctity of the elections. As long this research, the general election event is overshadowed by concerns regarding presidential neutrality in the electoral contest. This is further compounded by the term 'cawe-cawe', which has recently emerged, and indications of power misuse within intelligence agencies by President Joko Widodo, leading to increased suspicions about his neutrality and its impact on the electoral process. This study examines the correlation between elections and good governance, particularly how the perceived non-neutrality of the President may affect the achievement of good governance in Indonesia. The research aims to analyze the relationship between the implementation of general elections and the dimensions of good governance, both economic and social. This systematic reviews employs a conceptual and comparative approach, presenting data on the quality of Indonesian governance and economic growth during the election years of 2014 and 2019. The comparison aspect included good governance and economic growth in the years before, during, and after the elections.